Efektivitas pelatihan permainan sisi kecil pada akurasi passing pemain sepak bola muda - Rahmania Putri, Riska; Syafaruddin, Syafaruddin; Aryanti, Silvi; Destriani, Destriani; Yusfi, Herri (Universitas Nusantara PGRI Kediri, 2023)
The research aimed to determine the effect of small-side game training on the passing accuracy of young soccer athletes Farmel Hatta Palembang. The research method used in this study is experimental. The research design used was a pretest-posttest group design. The sampling technique used in this study used all members of the population in a youth soccer team of 40 players. The analysis techniques used are normality tests, homogeneity tests, and paired sample tests using the SPSS program version 26. The result obtained from the normality test (Kolmogorov-Smirnov Test) for the pre-test data was 0.56, and the post-test data was 3.28, so the data obtained from the pre-test and post-test were normal. The homogeneity test results show that the sig p is 0.633>0.05. Then the results of the hypothesis test obtained are t count 10.801 and t table 1.685 (df 39) with a sig (2-tailed) value of 0.000, so that small-sided game practice greatly influences the results of passing accuracy. Based on the research results on the impact of small game training, it fully affects the passing accuracy of young athletes of the FIFA football school Farmel Hatta Palembang.